Effect of certain drugs on blood biochemical profiles in cross breed cattle
The study was conducted on 60 1::ross bred cows which calved before three months but did not come into heat. Various drugs viz., Receptal (gr I), Urimin (gr 11), Minerex 6olus (gr III), Urimin plus Receptal (gr IV), Minerex bolus plus Receptal (gr V) were used to induce estrus and one gr was kept as control (gr VI). Levels .of calcium, phosphorus, zinc and copper were estimated in blood serum samples collected before treatment (0-day) and after treatment (on the day of first estrus) and those were found in increasing trend in all the groups on day of first estrus. Highest levels of zinc (286.70±14.980 mg/100 ml